An assessment of awareness, knowledge and perception of monkeypox (mpox) disease among internet users in Nigeria: a cross-sectional survey - Omotayo Olojede; Damola Bakare; Abiodun Sogbesan; Julius Salako; Ayobami Bakare (Babcock University Medical Journal)
Objectives: This study aimed to assess knowledge and perception of mpox among internet users in Nigeria.